Trabecular Fracture Zone Might Not Be the Higher Strain Region of the Trabecular Framework - Tassani, Simone; Pani, Martino; Noailly, Jerome; Gonzalez Ballester, Miguel Angel (Frontiers in Materials, 2018)
Trabecular bone fracture is a traumatic and localized event studied worldwide in order to predict it. During the years researchers focussed over the mechanical characterization of the trabecular tissue to understand its mechanics. Several studies pointed out the very local nature of the trabecular failure, finally identifying the fracture zone with the aim to study it separately. The complexity of the three-dimensional trabecular framework and the local nature of the fracture event do not allow the direct evaluation of a single trabecula’s behaviour within its natural environment. For this reason, micro-Finite Element Modelling have been seen as the best way to investigate this biomechanical issue. Mechanical strain analysis is adopted in the literature for the identification of micro fracture using criteria based on principal strains. However, it was never verified if the fracture zone is actually the zone where principal strains are concentrated. Here we show how the maximum strain of the tissue might not be directly correlated to the fracture. In the present work a previously validated technique was used to identify the fracture zone of 10 trabecular specimen mechanically tested in compression and scanned in micro-CT before and after the mechanical test. Before-compression datasets were used to develop 10 micro-FE models were the same boundary conditions of the mechanical test were reproduced. Our results show how the known linear behaviour of the trabecular framework might not be directly related to the development of the fracture suggesting other non-linear phenomenon, like buckling or micro-damage, as actual cause of the traumatic event. This result might have several implications both in micro-modelling and in clinical applications for the study of fracture related pathology, like osteoporosis.